an-4an-1+4an-2=(n+2)2

Simple and best practice solution for an-4an-1+4an-2=(n+2)2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for an-4an-1+4an-2=(n+2)2 equation:


Simplifying
an + -4an + -1 + 4an + -2 = (n + 2) * 2

Reorder the terms:
-1 + -2 + an + -4an + 4an = (n + 2) * 2

Combine like terms: -1 + -2 = -3
-3 + an + -4an + 4an = (n + 2) * 2

Combine like terms: an + -4an = -3an
-3 + -3an + 4an = (n + 2) * 2

Combine like terms: -3an + 4an = 1an
-3 + 1an = (n + 2) * 2

Reorder the terms:
-3 + 1an = (2 + n) * 2

Reorder the terms for easier multiplication:
-3 + 1an = 2(2 + n)
-3 + 1an = (2 * 2 + n * 2)
-3 + 1an = (4 + 2n)

Solving
-3 + 1an = 4 + 2n

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 1an = 4 + 3 + 2n

Combine like terms: -3 + 3 = 0
0 + 1an = 4 + 3 + 2n
1an = 4 + 3 + 2n

Combine like terms: 4 + 3 = 7
1an = 7 + 2n

Divide each side by '1n'.
a = 7n-1 + 2

Simplifying
a = 7n-1 + 2

Reorder the terms:
a = 2 + 7n-1

See similar equations:

| 229+50=X | | Tx=7-x | | (2/5)(-4+1x)=x/5 | | (5+3a)-(10a-5)=-22 | | 10x-63=-x+91 | | 5*20+8= | | t^7-t^2= | | (1/4)x-8=-9-(3/4)x | | 10+2x=x+14 | | -154-5x=49+2x | | 4x^2+25y^2=0 | | 5(4x-3)+12x= | | 12m^2/-18m^3 | | (5x+8)+(3x-8)+x=180 | | -4=0.75*4+x | | C/y | | Y=a/bx*c | | -4-(4-3p)= | | 4x(11-7x)= | | 15b+3b^5= | | (2-y)= | | 0=-2x^2+40x+5 | | 17.5+4x=6.5(3x-6) | | 8y-5=3(2-y) | | 6x/5•1/4x | | -6x-3x+12x-4=-1 | | 9n+12=15n-6 | | 8=e/-7 | | 9x-96=6x-9 | | 2/3x^-1/3=0 | | an-7an-1+10an-2=4n | | (2k^2-4k+5)=0 |

Equations solver categories